2012
DOI: 10.1155/2012/236956
|View full text |Cite
|
Sign up to set email alerts
|

Continuous and Long-Term Measurement of Reticuloruminal pH in Grazing Dairy Cows by an Indwelling and Wireless Data Transmitting Unit

Abstract: The aim of the present study was the continuous measurement of ruminal pH in grazing dairy cows to monitor the diets effects on ruminal pH value. A novel indwelling pH-measurement and data transmitting system was given to 6 multiparous cows orally. Ruminal pH was measured every 600 sec over a 40 d period. After barn feeding and changeover to pasture, the following 3 treatments (2 cows/treatment) were included in the measurement period: continuous grazing (G), continuous grazing plus 4 kg/d of hay fed twice dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 26 publications
2
28
0
Order By: Relevance
“…These units (3.5 cm i.d., 12 cm long, and weighing 210 g) were manually inserted into the reticulorumen via the esophagus (Gasteiner et al, 2012) in all cows on d 17 postpartum. Prior to this, the units were calibrated by a 2-point calibration using a buffer of pH 4.0 and one of pH 7.0 following the company's instruction protocol.…”
Section: Reticuloruminal Ph and Temperaturementioning
confidence: 99%
“…These units (3.5 cm i.d., 12 cm long, and weighing 210 g) were manually inserted into the reticulorumen via the esophagus (Gasteiner et al, 2012) in all cows on d 17 postpartum. Prior to this, the units were calibrated by a 2-point calibration using a buffer of pH 4.0 and one of pH 7.0 following the company's instruction protocol.…”
Section: Reticuloruminal Ph and Temperaturementioning
confidence: 99%
“…It can be concluded that SARA might occur under practical conditions in dairy cows during a period of feed changeover and when pasture feeding is combined with the supplemental feeding of grain-based concentrates. The indwelling pH measuring device is a very helpful tool and can also be used for practical purposes (Gasteiner et al 2012). In a previous study, Enemark et al (2003) used devices which were initially developed for marine animals and observed a slightly positive electrode drift after ten days of continuous application in the reticulorumen of cows.…”
Section: Introductionmentioning
confidence: 99%
“…Although the rumen pH has traditionally been used to diagnose SARA, (4) foreign objects in the rumen tend to eventually get transferred to the reticulum because of the rumen movements and then remain there indefinitely. (5) It has been shown that, although the pHs in the rumen and reticulum correlate well, they differ with that in the reticulum exhibiting a smaller pH drop in relation to SARA. (6) However, the reticulum is smaller than the rumen and there is evidence suggesting that this leads to a more stable pH, (7) so the smaller pH drop might be manageable.…”
Section: Introductionmentioning
confidence: 99%